The Role of Environment in Improving Learning Quality: A Case Study of Al-Istiqamah Modern Islamic Boarding School - Rara Pratiwi; Kamaruddin Kamaruddin; Adawiyah Adawiyah (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC EDUCATION, 2020)
This study examines the role of learning environment in improving the quality of learning students in modern boarding school Al-Istiqamah Ngatabaru. Research method used in this research is qualitative method with a case study approach. The data were collected through observation, semistructured interview, and documentary study. Data then analyzed through three stages, namely data reduction, display data and conclusion drawing/verification. The research results show that the role of learning environment in improving the quality of learning cases in modern boarding school Al-IstiqamahNgatabaru has a big role so that it affects the achievement of students. Based on the results of research in the field of Islamic boarding school learning environment role is the formation of students through the system pengasramaan, student character formation with the assignment, and the creation of a conducive learning. Supporting learning factors include good classroom, organized learning system, teaching program (TMI), curriculum management, while learning inhibiting factors include teachers demanded for professionals, influences coming from within students and surrounding areas, and inadequate facilities.